Internationalisation Process of A Coffee Producer: Born Global and Effectuation Logic - Novika Candra Astuti (Jurnal Indonesia Sosial Teknologi, 2024)
The entrepreneurial process of young exporters in the coffee industry in Indonesia lacks investigation. This study examines how a young company in the coffee industry is able to enter international markets early and rapidly since its inception called a born global company. Effectuation theory was employed to understand how entrepreneurs in the coffee industry made decisions and behaved in pursuing international opportunities. Data was collected through an exploratory case study of a born global firm in the coffee industry in Aceh, Sumatra, Indonesia by doing a semi-structured interview with the CEO of a co-operative. The study's findings revealed that a born global company applied the effectuation logic both in the new venture creation and in the early stage of the internationalisation process. According to the effectuation theory, the entrepreneur's network of domestic partners and prior experience allowed the business to quickly join the international market. The results showed that serendipity discovery was a key factor that enabled early internationalisation to occur. Moreover, serendipity discovery played a role as a base of a cognitive source of opportunity discovery and entrepreneurial acquisition of knowledge of international opportunities.